Functional circuit architecture underlying parental behaviour - Kohl, Johannes; Babayan, Benedicte M.; Rubinstein, Nimrod D.; Autry, Anita E.; Marin-Rodriguez, Brenda; Kapoor, Vikrant; Miyamishi, Kazunari; Zweifel, Larry S.; Luo, Liqun; Uchida, Naoshige; Dulac, Catherine (Nature (London), 2018)
Parenting is essential for the survival and wellbeing of mammalian offspring. However, we lack a circuit-level understanding of how distinct components of this behaviour are coordinated. Here we investigate how galanin-expressing neurons in the medial preoptic area (MPOA Gal ) of the hypothalamus coordinate motor, motivational, hormonal and social aspects of parenting in mice. These neurons integrate inputs from a large number of brain areas and the activation of these inputs depends on the animal’s sex and reproductive state. Subsets of MPOA Gal neurons form discrete pools that are defined by their projection sites. While the MPOA Gal population is active during all episodes of parental behaviour, individual pools are tuned to characteristic aspects of parenting. Optogenetic manipulation of MPOA Gal projections mirrors this specificity, affecting discrete parenting components. This functional organization, reminiscent of the control of motor sequences by pools of spinal cord neurons, provides a new model for how discrete elements of a social behaviour are generated at the circuit level. Galanin-expressing neurons in the medial preoptic area coordinate different aspects of motor, motivational, hormonal and social behaviour associated with parenting by projecting to different brain regions depending on the type of behaviour and sex and reproductive state of mice.